2023
DOI: 10.29333/iji.2023.1616a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Digital Drama-Based Instruction on Developing Receptive and Expressive Language among Kindergarten Children

Abstract: Young children need to mentally retrieve and express words aloud. They also need understood words when they are heard or read. The purpose of this study was to gain insight into the potential effects of digital drama -based instruction on developing receptive and expressive language among kindergarten children. This study employed a quantitative approach using a quasi-experimental, pre-test and post-test and follow up design. Sixty students were randomly chosen from public kindergartens. The kindergartens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a study of pre-kindergarten programmes, teacher attributes predicted observed learning quality in the classroom (Pianta et al, 2005). Mohamed & Barakat (2023) found that effective instruction by using digital drama-based methodology can lead to better receptive and expressive language outcomes of kindergarten children.…”
Section: Teaching Effectivenessmentioning
confidence: 99%
“…In a study of pre-kindergarten programmes, teacher attributes predicted observed learning quality in the classroom (Pianta et al, 2005). Mohamed & Barakat (2023) found that effective instruction by using digital drama-based methodology can lead to better receptive and expressive language outcomes of kindergarten children.…”
Section: Teaching Effectivenessmentioning
confidence: 99%
“…The existence of media that is creatively made by educators and varied in color and shape will stimulate children to be interested and want to persist in learning activities designed by educators (Koçyigit et al, 2020;Barakat, 2022). The child's interest in learning will certainly make the stimulation goals carried out well achieved.…”
Section: Early Childhood Learning Mediamentioning
confidence: 99%
“…Product implementation using digital technology encourages students' thinking processes, improves self-regulation ability, and actively generates new ideas in every teaching and learning activity (Sumarwati et al, 2020). Digital product-based learning effectively improves students' creativity, where students are inspired to motivate themselves and manage their self-regulation abilities in solving problems (Arjaya et al, 2023;Barakat, 2023;Behnamnia et al, 2020;Sholehuddin et al, 2023). The application of integrated learning in the assessment of digitized media increases creativity (Lashari et al, 2022;Sajidan et al, 2022).…”
Section: The Development Of Digital E-books To Improve Students' …mentioning
confidence: 99%